Gottesbegriff und Gotteserkenntnis bei Constantin Brunner und Martin Buber - Werner, Hans (Aschkenas, 2019)
The concept of God plays a prominent role in both Constantin Brunner’s and Martin Buber’s writings. In the way they treated this subject there are similarities, but also some striking differences. Both thinkers saw their philosophy as an attempt to explain the Absolute (Brunner) or God (Buber). Both were influenced by the philosophy of Spinoza and the tradition of mysticism. The crucial difference between Brunner and Buber is that Buber thinks of God as a person with whom a personal relationship is possible. Brunner, on his part, rejects any form of anthropomorphism and thinks of God as the Absolute, as an impersonal, unifying principle. Both interpretations point to a different understanding of religion and Judaism. For Brunner, Buber’s concept of God was an example of »superstition«, whereas Buber would have argued that Brunner does not understand the role of the Jewish God as a partner in dialogue.